Question
upstudy study bank question image url

\( 3 y+x=2 \) and \( y^{2}+x=x y+y \)

Ask by Erickson Ryan. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \(x = -1, y = 1\) and \(x = 0.5, y = 0.5\).

Solution

Solve the system of equations \( 3y+x=2;y^{2}+x=x*y+y \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y+x=2\\y^{2}+x=xy+y\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2-3y\\y^{2}+x=xy+y\end{array}\right.\) - step2: Substitute the value of \(x:\) \(y^{2}+2-3y=\left(2-3y\right)y+y\) - step3: Simplify: \(y^{2}+2-3y=3y-3y^{2}\) - step4: Move the expression to the left side: \(y^{2}+2-3y-\left(3y-3y^{2}\right)=0\) - step5: Calculate: \(4y^{2}+2-6y=0\) - step6: Factor the expression: \(2\left(y-1\right)\left(2y-1\right)=0\) - step7: Divide the terms: \(\left(y-1\right)\left(2y-1\right)=0\) - step8: Separate into possible cases: \(\begin{align}&y-1=0\\&2y-1=0\end{align}\) - step9: Solve the equation: \(\begin{align}&y=1\\&y=\frac{1}{2}\end{align}\) - step10: Calculate: \(y=1\cup y=\frac{1}{2}\) - step11: Rearrange the terms: \(\left\{ \begin{array}{l}x=2-3y\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=2-3y\\y=\frac{1}{2}\end{array}\right.\) - step12: Calculate: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1}{2}\\y=\frac{1}{2}\end{array}\right.\) - step13: Check the solution: \(\left\{ \begin{array}{l}x=-1\\y=1\end{array}\right.\cup \left\{ \begin{array}{l}x=\frac{1}{2}\\y=\frac{1}{2}\end{array}\right.\) - step14: Rewrite: \(\left(x,y\right) = \left(-1,1\right)\cup \left(x,y\right) = \left(\frac{1}{2},\frac{1}{2}\right)\) The solutions to the system of equations \(3y+x=2\) and \(y^{2}+x=x*y+y\) are: 1. \(x = -1\) and \(y = 1\) 2. \(x = 0.5\) and \(y = 0.5\)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the solution for the equations \( 3y + x = 2 \) and \( y^2 + x = xy + y \), let's tackle this systematically. From the first equation, we can express \( x \) in terms of \( y \): \[ x = 2 - 3y \] Now, we can substitute this expression for \( x \) into the second equation: \[ y^2 + (2 - 3y) = (2 - 3y)y + y \] Simplifying both sides will help us find the values of \( y \): 1. Left-hand side: \[ y^2 + 2 - 3y \] 2. Right-hand side: \[ (2y - 3y^2) + y = 2y - 3y^2 + y = 3y - 3y^2 \] Now, equating both sides: \[ y^2 + 2 - 3y = 3y - 3y^2 \] This simplifies to: \[ y^2 + 2 - 3y - 3y + 3y^2 = 0 \] \[ 4y^2 - 6y + 2 = 0 \] We can use the quadratic formula \( y = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) where \( a = 4, b = -6, c = 2 \): \[ y = \frac{6 \pm \sqrt{(-6)^2 - 4 \cdot 4 \cdot 2}}{2 \cdot 4} \] \[ y = \frac{6 \pm \sqrt{36 - 32}}{8} \] \[ y = \frac{6 \pm 2}{8} \] So we have: 1. \( y = 1 \) 2. \( y = \frac{1}{2} \) Now substituting back to find \( x \): For \( y = 1 \): \[ x = 2 - 3(1) = -1 \] For \( y = \frac{1}{2} \): \[ x = 2 - 3\left(\frac{1}{2}\right) = 2 - \frac{3}{2} = \frac{1}{2} \] Thus, the solutions to the system are \( (x, y) = (-1, 1) \) and \( \left(\frac{1}{2}, \frac{1}{2}\right) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy